(untitled) (REVISTA NODO, 2021)
This article presents the development and challenges of the inclusion of the environmental dimension in regional planning from the paradigm of sustainable development, in some Latin American countries, especially in the Colombian case. It is a descriptive study with qualitative methods of documentary research (Uribe, 2013), for informative and argumentative (Alfonzo, 1994) to try to resolve the question: ¿What have been the developments, after 26 years of initial approach from the countries of Latin America Own An Agenda Towards Sustainable Development, as one of the strategies to regional planning, especially in the Colombian case? The results point out that the inclusion of environmental dimensions in the present, use in the content of the European Charter of Land Management (1983), which looks at the interrelationship between man and nature, like the environmental and social dimension. This as a result of the inclusion of environmental dimensions in the economic development in the 60s, Product Initiatives Club of Rome and its report on the Limits to Growth, and then more strongly with the emergence of the paradigm of Sustainable Development. On the other hand, other states that the use land in the associate Colombian case, own more than a single public policy on land use planning a un joint sectoral public policies, mainly about: sustainable development (Law 99/93) the economic and social development (Law 152/94), and territorial and urban development (Law 388/97), amongst others. Synthesis and country planning is a duty of the State, which is a matter of policy and a matter of power. Thus, it is necessary, by the Colombian state, to take on the challenge of exploring new hybrid approaches (from top to bottom and bottom-up), where the administrative political divisions of geographical space expire and enable the un sustainable land management. This tends towards harmonization of natural, social and economic dimensions, and is very safe, thus they will be tangible in the practice, through the motions figures in the LOOT (Law 1454/2011).